PERBANDINGAN KINERJA BANK BERDASARKAN ANALISIS RASIO RENTABILITAS - IDA ZUNIARTI (Universitas Bina Sarana Informatika, 2014)
Bank is an industry which main activity is to mobilize funds from public and then distribute it in order to earn income. Therefore, it is important for banks to maintain public’s trust because its business is to rely on public’s trust. One of some attempts to maintain public’s trust is by increasing the performance of the bank institution itself.This research aims to determine the differences in the financial performance of the bank with a case study is PT Bank Mandiri (Persero), Tbk and PT Bank Central Asia (Persero), Tbk period 2002 – 2012. The data processing in this research performed using statistical techniques such as average two different test (independent sample T-Test). The puRp.ose of testing the hypothesis of average two different test on this research is to accept or reject the hypothesis that has been made. The data being used is secondary data which is the statements of published financial such as balance sheet and income statement obtained from the website of Bank Indonesia (www.bi.go.id).The performance of the two banks are measured using the financial ratio, Return on Assets ratio (ROA), Return on Equity (ROE), Net Interest Margin (NIM), Operating Expenses/ Operating Income (BOPO). The result of this research which uses financial ratio analysis shows that the performance of BCA is better than Bank Mandiri during the period 2002 – 2012. The overall financial performance shows that BCA has better financial performance than Bank Mandiri. The average value of ROA from Bank Mandiri period 2002 – 2012 is 2,3280, and BCA is 3,1780. The average value of ROE from Bank Mandiri is 16,3510, and BCA is 23,1040. The average value of NIM from Bank Mandiri is 3,9110 and BCA is about 4,7090. And the average value of BOPO from Bank Mandiri is 75,4210 and BCA is 67,6660. Keywords : Comparative Analysis, ROA, ROE, NIM and BOPO